The dynamics of TNF-α and IFN-γ content in adult patients with measles depending on the severity of the disease - O. V. Riabokon; S. O. Bilokobyla; Yu. Yu. Riabokon; N. V. Onishchenko (Kazimierz Wielki University, 2021)
Background. Measles is an acute viral infection, predominantly of childhood ages. However, in recent years, the incidence of measles among adults has significantly increased, with the development of a severe and complicated course of the disease. Materials and methods. The study included 175 patients with measles and 30 healthy people. The quantitative content of TNF-α and IFN-γ in blood serum was determined by enzyme-linked immunosorbent assay. Statistical processing was performed in program "STATISTICA for Windows 13" (StatSoft Inc., No. JPZ804I382130ARCN10-J). Results. A study of 175 measles patients found the frequency and spectrum of complications in adult patients depending on the severity of the disease and dynamics of TNF-α and IFN-γ level in blood serum. It is shown that frequency and range of complications in adult patients with measles depends on the severity of the disease. Patients with severe measles were more likely to develop complications from the respiratory system (p <0.01) due to the formation of pneumonia (p = 0.0001) and from the gastrointestinal tract with more frequent development of hepatitis (p = 0.0001) and enteritis (p = 0.0001), compared with moderate patients. In patients with severe measles, content of TNF-α in blood serum is the highest and exceeds both corresponding rate of healthy individuals (p <0.05) and measles patients with moderate course (p <0.05). Higher levels of TNF-α in the serum of measles patients during rash period are associated with severe course of the disease (p = 0.008). At the time of hospitalization of adult patients with measles during the rash IFN-γ content in the serum is higher (p <0.05) than in healthy individuals, both in patients with severe (p <0.05) and moderate course of measles (p <0.05). In the dynamics of IFN-γ content in the serum patients of both study groups decreases (p <0.05), compared with hospitalization, and at the time of discharge is not statistically different from that of healthy people (p> 0.05). Conclusions. Patients with severe measles compared with moderate measles patients more likely developed complications from respiratory system (p <0.01) and gastrointestinal system (p <0.01). In patients with severe measles, content of TNF-α in blood serum is highest that corresponding rate of healthy individuals (p <0.05) and patients with moderate course (p <0.05). At the hospitalization time during the rash IFN-γ content in the serum is higher (p <0,05) than in healthy individuals, both in patients with severe (p <0,05) and with moderate measles (p <0,05).